Molecular characterisation of Fusarium species causing common bean root rot in Uganda - Erima, S.; Nyine, M.; Edema, R.; Nkuboye, A.; Habiba, N.; Candiru, A.; Paparu, P. (2025)
Recently, Fusarium root rot (FRR)-like symptoms were observed in Uganda’s agroecology zones, prompting the National Agricultural Organisation (NARO) to conduct a disease survey. The survey reports indicated FRR as the second most prevalent root rot disease of common bean in Uganda after Southern blight. Ninety nine Fusarium spp. strains were obtained from samples collected during the surveys. The strains were morphologically and pathogenically characterised and confirmed to cause Fusarium root rot as observed in the field. However, molecular characterization of the strains was not conducted. In this study therefore, 80 of the strains were characterized using partial sequences of translation elongation factor 1-alpha (TEF-1α) gene, beta tubulin (β tubulin) gene and internal transcribed spacers (ITS) region of ribosomal RNA to determine species diversity. High quality Sanger sequences from the target genes were compared to the sequences from Fusarium species available in the National Centre for Biotechnology Information coding sequences (NCBI-CDS) database to determine the most likely species the strains belonged. The sequences from our strains were deposited into the NCBI gene bank under ID# 288420, 2883276, 2873058 for TEF-1α, β tubulin and ITS respectively. The Fusarium species identified included; F. Oxysporum, F. solani, F. equiseti F. delphinoides, F. commune, F. subflagellisporum, F. fabacearum, F. falciforme, F. brevicaudatum, F. serpentimum, F. fredkrugeri and F. brachygibbosum. The diversity of these Fusarium species needs to be taken into consideration when developing breeding programs for management of the disease since currently there is no variety of common bean resistant to FRR in Uganda.